A bis-Phenolate Carbene-Supported bis-μ-Oxo Iron(IV/IV) Complex with a [FeIV(μ-O)2FeIV] Diamond Core Derived from Dioxygen Activation - Gravogl, Lisa; Kass, Dustin; Pyschny, Oliver; Heinemann, Frank Wilhelm; Haumann, Michael; Katz, Sagie; Hildebrandt, Peter; Dau, Holger; Swain, Abinash; García-Serres, Ricardo; Ray, Kallol; Munz, Dominik; et al. (Journal of the American Chemical Society, 2024)
The diiron(II) complex, [(OCO)Fe(MeCN)]2 (1, MeCN = acetonitrile), supported by the bis-phenolate carbene pincer ligand, 1,3-bis(3,5-di-tert-butyl-2-hydroxyphenyl)benzimidazolin-2-ylidene (OCO), was synthesized and characterized by single-crystal X-ray diffraction, 1H nuclear magnetic resonance, infrared (IR) vibrational, ultraviolet/visible/near-infrared (UV/vis/NIR) electronic absorption, 57Fe Mossbauer, X-band electron paramagnetic resonance (EPR) and SQUID magnetization measurements. Complex 1 activates dioxygen to yield the diferric, μ-oxo-bridged complex [(OCO)Fe(py)(μ-O)Fe(O(C═O)O)(py)] (2) that was isolated and fully characterized. In 2, one of the iron-carbene bonds was oxidized to give a urea motif, resulting in an O(CNHC═O)O binding site, while the other Fe(OCO) unit remained unchanged. When the reaction is performed at −80 °C, an intensively colored, purple intermediate is observed (INT, λmax = 570 nm; ϵ = 5600 mol L-1 cm-1). INT acts as a sluggish oxidant, reacting only with easily oxidizable substrates, such as PPh3 or 2-phenylpropionic aldehyde (2-PPA). The identity of INT can be best described as a dinuclear complex containing a closed diamond core motif [(OCO)FeIV(μ-O)2FeIV(OCO)]. This proposal is based on extensive spectroscopic [UV/vis/NIR electronic absorption, 57Fe Mossbauer, X-band EPR, resonance Raman (rRaman), X-ray absorption, and nuclear resonance vibrational (NRVS)] and computational studies. The conversion of the diiron(II) complex 1 to the oxo diiron(IV) intermediate INT is reminiscent of the O2 activation process in soluble methane monooxygenases (sMMO). Most importantly, the low reactivity of INT supports the consensus that the [FeIV(μ-O)2FeIV] diamond core in sMMO is kinetically inert and needs to open up to terminal FeIV═O cores to react with the strong C-H bonds of methane.
CRIS-Team Scopus Importer:2024-10-25